2012
DOI: 10.1590/s1984-82502012000300025
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant and skeletal muscle relaxant effects of the aqueous extract of the Prosopis cineraria

Abstract: The aqueous leaves extract of Prosopis cineraria (AEPC) is used traditionally for the treatment of various CNS disorder. The purpose of this study was to evaluate the extract for antidepressant and skeletal muscle relaxant activity. The antidepressant effect of the extract was evaluated using Forced swim test (FST). The immobility periods of control and treated mice were recorded. The antidepressant-like effect of tested compound was compared to that of imipramine (15 mg/kg. p.o). Muscle relaxant property was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…Muscle relaxant activity was analyzed using rotarod apparatus and total fall off-time for standard and control group was measured. A significant decrease in immobility time duration in FST was observed (at a dose of 200 mg/kg of leaf extract), and the effect was similar to imipramine [81].…”
Section: Anti-depressive and Cns Disorders Effectsmentioning
confidence: 57%
“…Muscle relaxant activity was analyzed using rotarod apparatus and total fall off-time for standard and control group was measured. A significant decrease in immobility time duration in FST was observed (at a dose of 200 mg/kg of leaf extract), and the effect was similar to imipramine [81].…”
Section: Anti-depressive and Cns Disorders Effectsmentioning
confidence: 57%
“…NC: Negative Control FLX: Fluoxetine 20 mg/kg TEP 50: Alpha-Terpineol 50 mg/kg TEP100: Alpha-Terpineol 100 mg/kg Thus, preclinical experimental studies using mice and behavioral testing protocols are of paramount importance to assess the effectiveness of substances with potential antidepressants. In one of these trials, there was a reduction in the immobility time of mice in FST, when they received Proposis cineria at a dose of 200 mg/kg compared to the control group, demonstrating significant antidepressant activity and relaxation of skeletal muscle (George, Joseph, & Sharma, 2012). The same effect was verified by Mendonça-Netto et al (2008) when using a fraction of total tertiary alkaloids 12 mg/kg of Cissampelos sympodialis Eichler (Menispermaceae).…”
Section: Subtitlementioning
confidence: 76%
“…The adapted test by Gonçalves et al (2008) by Montenegro, Sena, Barbosa Filho and Almeida (2010) and Nogueira Neto et al (2012) measures the effect of muscle relaxation or impaired motor coordination produced by compounds in animals.…”
Section: Rota-rod Testmentioning
confidence: 99%
“…However, no study has been published in scientific journals that investigated the effects of PFE on morphine withdrawal syndrome in rats. It has been reported that some species (i.e., P. spicigera ) exhibited significant antidepressant-like effect and skeletal muscle relaxant activity by using the forced swimming and tail suspension tests [ 25 ]. Another species of this genus, such as the P. juliflora , has been shown to stimulate the immune system [ 26 ] and function as an acetylcholinesterase inhibitor and butyrylcholinesterase inhibitor with Ca2+ channel blocking activity [ 27 ].…”
Section: Discussionmentioning
confidence: 99%